Greetings.
Solving by substitution, we can substitute either y-term or x-term. For a fast and better way, I recommend you to substituting x-term.
![- x + 3y = 7 \\ x - 4y = - 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/4bbuv56i5g7x06md1a1hmrnqlx9qazq9dc.png)
Because for x-term, we don't have to move the coefficient to another side as the coefficient for x-terms are both - 1 and 1.
What we need to do is that we move everything to another side excluding x-term.
I will be moving the second equation to another side.
![x = - 10 + 4y](https://img.qammunity.org/2021/formulas/mathematics/high-school/n3e4hc4ainlup52p5prc5oob8pv6lj9lje.png)
Now our x-term for the seco d equation is - 10+4y.
Substitute x =-10+4y in the first equation.
![- ( - 10 + 4y) + 3y = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/tf1pb5ggeuknl1l08ew3pxl5twdgy01oue.png)
We should get like this. Then we distribute the negative sign in the brackets.
![10 - 4y + 3y = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/cgcnws67p2gu3i345lgqrmpysnb1x0ekpl.png)
Remember that negative multiplying negative equal positive.
![- y + 10 = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/sp812pn2vg69mvm5svesutqjj54vntzf04.png)
Subtract as we get -y then we move 10 to another side, leaving y as the subject.
![- y = 7 - 10 \\ - y = - 3 \\ y = ( - 3)/( - 1) \\ y = 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/zfz578nobphktrkfo7bsa6hg5q4eoecsfb.png)
Also negative dividing negative equal positive as well. We have the y-value but because it is the two equations. We need to find the x-value as well.
Therefore, substituting y-value in any given equations. It is better to substitute y-value in the equation with less coefficient value.
I will be substituting y-value in the first equation.
![- x + 3y = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/qu4n4wxkhbtumn5a12mafgmkhvx4nswwsa.png)
Substitute y = 3 in the equation.
![- x + 3(3) = 7 \\ - x + 9 = 7 \\ - x = 7 - 9 \\ - x = - 2 \\ x = ( - 2)/( - 1) \\ x = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ga2581rmctvvmjik3h862fs4kfv9acejcp.png)
Answer in coordinate point/ordered pair as we get (2,3)